2015
DOI: 10.1039/c5fd00025d
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen deficient layered double perovskite as an active cathode for CO2 electrolysis using a solid oxide conductor

Abstract: A-site ordered PrBaMn2O(5+δ) was investigated as a potential cathode for CO2 electrolysis using a La(0.9)Sr(0.1)Ga(0.8)Mg(0.2)O3 (LSGM) electrolyte. The A-site ordered layered double perovskite, PrBaMn2O(5+δ), was found to enhance electrocatalytic activity for CO2 reduction on the cathode side since it supports mixed valent transition metal cations such as Mn, which could provide high electrical conductivity and maintain a large oxygen vacancy content, contributing to fast oxygen ion diffusion. It was found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 29 publications
2
51
0
Order By: Relevance
“…The challenges associated with materials are more fundamental in nature, and the degradation mechanism in SOECs is not yet well understood. It is generally agreed that more R&D is warranted toward designing new electrode materials like double perovskites (Shin et al, 2015;Afroze et al, 2019;Tian et al, 2020) or modification of existing electrodes. When CO 2 is added to steam for generation of syngas (mode 2), the issues related to the stability of the electrode become even more challenging.…”
Section: Challenges and Advancement In The Electrolytic Production Ofmentioning
confidence: 99%
“…The challenges associated with materials are more fundamental in nature, and the degradation mechanism in SOECs is not yet well understood. It is generally agreed that more R&D is warranted toward designing new electrode materials like double perovskites (Shin et al, 2015;Afroze et al, 2019;Tian et al, 2020) or modification of existing electrodes. When CO 2 is added to steam for generation of syngas (mode 2), the issues related to the stability of the electrode become even more challenging.…”
Section: Challenges and Advancement In The Electrolytic Production Ofmentioning
confidence: 99%
“…In particular, the manganite, PrBaMn2O5+ was found to be stable both as SOFC anode withstanding sulfur contamination and carbon deposition when operating on direct hydrocarbons 10 and as a SOEC cathode for high temperature electrochemical CO2 electrolysis 11 . Furthermore, the structurally related NdBaMn2O5+ compound was shown to be a potential electrode material for symmetrical SOFCs 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, mixed ionic–electronic conducting (MIEC) perovskite oxides, such as strontium titanate (SrTiO 3 )‐based oxides and lanthanum chromate (LaCrO 3 )‐based oxides, have been explored as the potential cathode materials because these cathode materials have demonstrated excellent stability at the elevated temperature for directly electrolyzing CO 2 to CO without the addition of any safe gas (usually H 2 , CO, or H 2 –CO mixture). [ 4 ] However, their performance is still insufficient for practical CO 2 RR application. Therefore, further modification still needs to be done to efficiently enhance the cathode performance to enable direct CO 2 electrolysis.…”
Section: Figurementioning
confidence: 99%
“…[ 5 ] Previous studies have revealed that the introduction of oxygen vacancies at the cathode surface could not only effectively accelerate the CO 2 chemical adsorption, but also significantly reduce the energy barrier of CO 2 dissociation, possibly facilitating the direct CO 2 RR. [ 6 ] Metallic nanoparticles have been commonly introduced into the perovskite oxide cathodes to effectively alter the electrocatalytic properties of the cathodes, and to significantly increase the concentration of oxygen vacancies, resulting in a remarkable improvement of CO 2 adsorption and activation [4d,5b,7] . Therefore, it is highly expected to construct metallic nanoparticles–decorated perovskite oxide cathodes for efficient CO 2 RR.…”
Section: Figurementioning
confidence: 99%